2023
DOI: 10.3390/microorganisms11082000
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of Potential Linkages between Biocide Tolerance and Antibiotic Cross-Resistance

Abstract: Antimicrobials (e.g., antibiotics and biocides) are invaluable chemicals used to control microbes in numerous contexts. Because of the simultaneous use of antibiotics and biocides, questions have arisen as to whether environments commonly treated with biocides (e.g., hospitals, food processing, wastewater, agriculture, etc.) could act as a reservoir for the development of antibiotic cross-resistance. Theoretically, cross-resistance could occur if the mechanism of bacterial tolerance to biocides also resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 128 publications
0
0
0
Order By: Relevance
“…These authors suggested that after the function of AOB was inhibited, AOA with the same ecological function was further strengthened, thereby supplementing the functional deficiency of AOB (functional redundancy between AOA and AOB). There were significant differences in the effects of the three antibiotics on AOA amoA and AOB amoA, indicating that ammonia-oxidizing microorganisms have different sensitivities to various antibiotics, which may be due to the degree of tolerance and adaptation of microorganisms to antibiotics [42]. OTC had the strongest inhibitory effect on nosZ gene abundance, which was consistent with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…These authors suggested that after the function of AOB was inhibited, AOA with the same ecological function was further strengthened, thereby supplementing the functional deficiency of AOB (functional redundancy between AOA and AOB). There were significant differences in the effects of the three antibiotics on AOA amoA and AOB amoA, indicating that ammonia-oxidizing microorganisms have different sensitivities to various antibiotics, which may be due to the degree of tolerance and adaptation of microorganisms to antibiotics [42]. OTC had the strongest inhibitory effect on nosZ gene abundance, which was consistent with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Biocidal substances act in different ways and sometimes several biocides are combined within a single product to increase the overall antimicrobial efficacy [8]. The mechanisms of action and tolerance to a wide range of biocides on bacteria have been reviewed and described widely in the literature [5,[9][10][11]. Biocides generally act on multiple targets unless present at sub-inhibitory or low concentration [8], although exact mechanisms of action are not fully understood, and are also organism specific.…”
Section: Use Of Biocides In Food Animal Productionmentioning
confidence: 99%
“…They also have antimicrobial properties and may be used for this purpose in food animal production. The antimicrobial modes/mechanisms of action of metals on bacteria have been reviewed and described in the literature [5,18,19]. As with biocides, the exact mechanisms of action still remain unclear and are also organism specific, but reported actions include effects on the cell wall or membrane; interactions with DNA; binding or inhibition of enzymes and membrane proteins.…”
Section: Use Of Metals In Food Animal Productionmentioning
confidence: 99%
See 2 more Smart Citations